2018
DOI: 10.1097/jom.0000000000001307
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Changes in Firefighters

Abstract: Objectives:Firefighters have elevated cancer incidence and mortality rates. MicroRNAs play prominent roles in carcinogenesis, but have not been previously evaluated in firefighters.Methods:Blood from 52 incumbent and 45 new recruit nonsmoking firefighters was analyzed for microRNA expression, and the results adjusted for age, obesity, ethnicity, and multiple comparisons.Results:Nine microRNAs were identified with at least a 1.5-fold significant difference between groups. All six microRNAs with decreased expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 78 publications
1
25
0
Order By: Relevance
“…In this context, miRNAs look as candidates with great potential, as they are present in any human biological fluid and can be isolated with commercial kits with no risk for the worker. As far as we know there are few studies investigating the role of miRNAs as novel biomarkers of occupational exposure, most of which have already been described in the introduction [9,10, 12,13]. One of these studies found in the recent scientific literature is similar to our investigation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this context, miRNAs look as candidates with great potential, as they are present in any human biological fluid and can be isolated with commercial kits with no risk for the worker. As far as we know there are few studies investigating the role of miRNAs as novel biomarkers of occupational exposure, most of which have already been described in the introduction [9,10, 12,13]. One of these studies found in the recent scientific literature is similar to our investigation.…”
Section: Discussionsupporting
confidence: 81%
“…Six miRNAs (miR-34a, miR-205, miR-10b, let-7d, miR-185 and miR-423-5p-2) were up-regulated and seven (miR-133a, miR-543, hsa-miR-130a, miR-27b, miR-223, miR-142-5p and miR-320b) were down-regulated when groups were compared to healthy controls (p ≤ 0.05) [12]. Another recent study conducted on firefighters exposed to several toxicants and carcinogens (benzene, polycyclic aromatic hydrocarbons, formaldehyde, arsenic, 1–3 butadiene, cadmium, chromium, asbestos, flame retardants and particulates) reports nine miRNAs with at least a 1.5-fold significant difference between fifty-two incumbent firefighters and forty-five newly employed nonsmoking firefighters [13]. These few publications highlight miRNAs role as biomarkers of exposure or of early effect and their applicability to the biomonitoring at workplace [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic modifications are critical steps in carcinogenesis and cancer prevention [ 17 , 18 ]. We have previously shown that microRNAs are differentially expressed between incumbent and new recruit firefighters [ 19 ], but published information on DNA methylation in firefighters to our knowledge has been limited to four genes [ 20 ]. DNA methylation refers to the addition of a methyl group to cytosine within 5'-C-phosphate-G-3' (CpG) dinucleotides, which are often concentrated in large clusters called CpG islands.…”
Section: Introductionmentioning
confidence: 99%
“…The literature has established that firefighters are at an increased risk for a variety of cancers including those of the kidney [ 3 - 5 ]. The mechanism for this increased risk is beyond the scope of our review, but is suspected to be due to exposure to carcinogens and possible genetic changes as a result [ 8 ]. RCC is one of the deadliest urological cancers.…”
Section: Discussionmentioning
confidence: 99%